The petroleum exploration of Ireland's offshore basins - Shannon, P.; Haughton, P. D. W.; Corcoran, D. V. (Geological Society, 2001)
This guide covers a wide range of exploration topics from the regional to the field scale. It provides new information on Neogene to recent stratigraphy and sedimentation in the North Atlantic.
Keywords: Petroleum -- Prospecting -- Ireland.; Petroleum -- Prospecting -- North Atlantic Ocean.; Petroleum -- Geology -- North Atlantic Ocean.; elektronické knihy; electronic books